Evaluation of 4 mm implants in mandibular edentulous patients with reduced bone height. Surgical preliminary results - J.L. Calvo-Guirado; M. Mallaun; M. Dard; J.A. López Torres (Ariesdue, 2014)
Aim: Growing evidence has suggested the utility of short dental implants for oral reconstructive procedures in clinical situations of limited vertical bone height. The aim of this short comunication was to evaluate the clinical use of implants < 10 mm in length and to determine short implant-supported prosthesis success in the atrophic jaw. Materials and methods: Six women and three men were recruited for the treatment of edentulous mandibles. A total of 6 implants were inserted in each patient: two anterior implants of conventional lenght and four posterior 4 mm Titanium Zirconium (TiZr) implants. The insertion torque and bone denisty were evaluated. Results: The mean insertion torque for the 4 mm implants was lower than for conventional ones, without any statistical difference. Moreover, most of the patients (88%) showed a D2 bone type. Conclusion: The provision of short implant-supported prostheses in patients with atrophic alveolar ridges appears to be a successful treatment option in the short term; however, more scientific evidence is needed for the long term.